Islamic psychotherapy: its significance and relevance in the empowerment of Islamic civilization / Che Haslina Abdullah ... [et al.] - Abdullah, Che Haslina; Razali, Wan Noorli; Taha, Mohd Marbawi; Kechil, Rafizah (2016)
Media has been inundated with reports on various criminal acts in the society. One of the reasons why these inhuman activities occur is due to the perpetrator’s mental illness or ailment of the soul. This mental state is often associated with stress which then lead to moral damage. The fall of Islamic civilization has long seen to be hugely contributed by decadence and moral decay among Muslims. Today, method of psychotherapy based on the Qur'an and Sunnah are seen as a highly relevant mechanism towards curing the stress of human psyche. The method is important in the formation of quality human personality in the world and the afterlife. A civilization may easily collapse if there is an absence of spiritual, emotional, mental and physical balance in its people. A qualitative research method, mainly library based research is used in the writing of this article. This article significance and relevance of psychotherapy method in building a Muslim identity as the foundation to strengthen Islamic civilization towards encountering various contemporary and future crises.